The toxic effects of copper on larvae of the barnacle species Chthamalus challengeri - 齐磊磊 王影 沙婧婧 王悠 唐学玺 (Chinese journal of oceanology and limnology, 2015)
With the increased use of copper （Cu）-based antifouling （AF） paints, copper has become a potential threat to marine organisms. Experiments were performed to investigate the effects of copper on larvae of the barnacle Chthamalus challengeri. These experiments attempted to identify a more sensitive index to monitor copper pollution in marine environments. The 24 h LC_50 ranged from 156.07 μg/L （nauplius Ⅱ） to 817.15μg/L （cypris） and the no observed effect concentration （NOEC） ranged from 81.75 μg/L （nauplius Ⅱ） to 571.04 μg/L （cypris）. The cypris settlement rate declined significantly when copper concentrations 〉135 μg/L. No cypris was found in the copper concentration of 60 and 75 μg/L treatment groups stressed for 22 d. Nauplius Ⅱ moulting was not affected by exposure to copper for 24 h; however, when extended to 48 h, the percent moulted in 75 μg/L treatment group was declined to 37.12%, which was significant lower （P〈0.05） than that in the control group. The phototaxis of nauplius II decreased significantly when copper concentrations _〉45 μg/L. Despite an initial significant increase at copper concentrations of 30 μg/L, ammonia excretion rate decreased when copper concentrations ≥60 μg/L. These results suggested that： （1） nauplius Ⅱ could not develop to the cypris when the copper concentration ≥60 μg/L; （2） cypris settlement is more susceptible to copper than cypris mortality rate; （3） nauplius II is the most sensitive larval stage; （4） nauplius II ammonia excretion rate is the most sensitive index to copper and might be as the indicator for copper pollution monitoring.